PENGARUH KERAGAMAN PRODUK, PERSEPSI HARGA DAN SHOP LOCATION TERHADAP PURCHASE DECISION KONSUMEN PADA DEWA AYU SHOP KLUNGKUNG - Kadek Asrilina Putrawan; Anak Agung Putu Agung; Ni Putu Cempaka Dharmadewi Atmaja (EMAS, 2022)
This study aims to determine the effect of product diversity, price perception, and store location on purchasing decisions at Dewa Ayu Klungkung Stores. Fashion today is very fulfilling human lifestyles that are very diverse in nature. The fashion store business competition is very tight, starting from the selection of products, surveys of people's desires and interests, offering prices that fit in the pocket, the right target market and strategic locations so that they are easy to visit or know by many people. The research population is all consumers who have transacted at the Dewa Ayu Klungkung fashion store. The sample in this study was 100 respondents who were determined based on the purposive sampling data collection method. The analytical tool used is multiple linear regression analysis. The results show that product diversity has a positive and significant effect on purchasing decisions, price perceptions have a positive and significant effect on purchasing decisions, and store location has a positive and significant effect on purchasing decisions. The suggestion of this research is because the coefficient of determination of the variable product diversity, price perception and store location is 36.7%, while the remaining 63.3% is caused by other factors, it is expected to be able to add other variables that can influence purchasing decisions. consumers, as well as being able to expand the scope of research that is not only limited to one location.